OHP-004 Evaluation of proper use and effectiveness of ceftaroline in our clinical practice. (25th February 2017) - Valentin, B; Debailleul, M; Pelloquin, N; Belhout, M; Mary, A
Abstract : Background: Ceftaroline is a broad spectrum antibiotic used to treat complicated skin and soft tissues infections and community acquired pneumonia. To prevent emergence of resistant strains and conserve its effectiveness, ceftaroline prescription should be limited to specific recommended cases. Purpose: The aim of this study was to evaluate proper use and effectiveness of ceftaroline in our establishment. Material and methods: This was a retrospective study performed between January 2014 and December 2015. Patients who received ceftaroline and their biological and clinical data were collected by extraction from our prescription software (DXCARE and CLINISOFT). Seven items analysed the 'correct use' of ceftaroline: clinical setting, indication, referred germ, sensibility to other antibiotics, dosage, advice from an infectious disease and type of treatment (empiric, prophylactic or reassessed). Four items evaluated the 'effectiveness': treatment time, time for negative culture result, minimum inhibitory concentration (MIC) and healing of the infection. Results: During the period, 13 patients received ceftaroline; 1 patient's record was unusable. Prescriptions for ceftaroline were off-label in 83.3% (10/12, in the majority for osteo-articular infection), and 83.3% (10/12) of prescriptions were documented with identification of a methicillin resistant staphylococcal (once associated with Escherichia coli and another with Haemophilus parainfluenza ). Each time, germs were resistant to glycopeptides. Dosage was adapted to renal function for 83.3% of cases and the last 2 cases benefited from pharmaceutical intervention to obtain adequate posology. Advice from an infectiologist was given for each treatment initiation. Average and median treatment time were, respectively, 15.5 days and 10 days. Average time to culture negative result was 9.2 days, but was assessed for osteo-articular and not documented infections (7/12). Ceftaroline MIC was measured in 6 cases and was strictly below 1 mg/mL. All patients were cured of their infection, with a minimum step back 6 months. No adverse reactions were observed during the study. Conclusion: This study showed important off-label use for ceftaroline but specialist advice was systematically requested due to the complexity of the patients. In all cases, patients were cured of their infection. Despite the off-label prescriptions, ceftaroline was used properly, with good therapeutic efficacy in our institution. A multicentre study should be performed to compare practices between several hospitals. No conflict of interest